2005
DOI: 10.1136/vr.156.2.41
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy and cross‐protectivity of a live intranasal aerosol haemorrhagic septicaemia vaccine

Abstract: The safety, efficacy and cross-protectivity of a live intranasal aerosol haemorrhagic septicaemia vaccine containing Pasteurella multocida serotype B:3,4 were tested in young cattle and buffaloes in Myanmar, where more than 1.5 million animals had been inoculated with this vaccine between 1989 and 1999. A recommended dose of 2 x 10(7) viable organisms was used for the efficacy test. The administration of 100 times the recommended dose to 50 cattle and 39 buffalo calves was innocuous. Seven months after they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In this study, mucosal immunity was targeted in this study as it could provide a substantial herd immunity coverage that requires no professional vaccine delivery and is needle‐less, pain‐free and no inflammation in the vaccinated site. No endotoxic or anaphylactic responses were also observed in the intranasal vaccinated animals, as shown in this study which is in accordance with the previous studies (Myint et al ; Owen et al ; Saleem et al ). Intranasal administration is more efficient than other routes as it can induce the mucosal immunity of the exposed host and also be able to transmit the antigens to the in‐contact hosts and thus provoke their mucosal immunity due to self‐vaccination (Zamri‐Saad and Annas ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, mucosal immunity was targeted in this study as it could provide a substantial herd immunity coverage that requires no professional vaccine delivery and is needle‐less, pain‐free and no inflammation in the vaccinated site. No endotoxic or anaphylactic responses were also observed in the intranasal vaccinated animals, as shown in this study which is in accordance with the previous studies (Myint et al ; Owen et al ; Saleem et al ). Intranasal administration is more efficient than other routes as it can induce the mucosal immunity of the exposed host and also be able to transmit the antigens to the in‐contact hosts and thus provoke their mucosal immunity due to self‐vaccination (Zamri‐Saad and Annas ).…”
Section: Resultssupporting
confidence: 94%
“…Previous studies have shown that intranasal vaccination is safer and provides longer lasting immunity without causing local inflammation or endotoxic shock (Myint et al . ; Saleem et al ). Furthermore, the serum antibodies, IgA and IgG, have also been shown to play an important role for the protection of the rat from the PMB2 infection challenge, as the serum antibodies were detectable in passive immunization.…”
Section: Resultsmentioning
confidence: 98%
“…The low antibody level of in-contact goats at challenge failed to protect. A similar study in calves vaccinated intranasally with high doses of live P. multocida B:3,4 revealed protection against subcutaneous low-dose challenge with P. multocida B:2 (Myint et al, 2005). When animals are exposed to an infectious agent, antibodies start to appear within approximately 5-7 days.…”
Section: Discussionmentioning
confidence: 84%
“…Twelve months after immunization, eight of eight cattle and three of four buffalo calves survived following subcutaneous challenge. Eventually, over one million cattle population was vaccinated using this vaccine during 1989 to 1999 in Myanmar indicating that live intra-nasal vaccines are safe and efficient for control of HS in endemic areas (Myint et al 2005).…”
Section: Discussionmentioning
confidence: 99%